Experimental protocol to repel opossums (Didelphis marsupialis) through an artisanal odor repellent device - Rodríguez, Karen N; Aguirre, Diana R; Ceballos, Claudia P (Revista Colombiana de Ciencias Pecuarias, 2022)
Background: The human-opossum (Didelphis marsupialis) conflict has increased during the last decades mainly due to natural habitat loss, and mediated by generalist and opportunistic habits of opossums. A potential solution to reduce this conflict is to discourage the presence of opossums in human settlements without affecting the welfare of either part. Objective: To develop an artisanal odor device and test three chemical substances (citronella, ammonia, and creolin) for their separate effectiveness to drive away opossums. Methods: We first attracted local opossums using fruits or canned sardines as bait in an urban natural park (n=2 sites) and a peri-urban forest reserve (n=4 sites), both located in the Municipality of Envigado, Province of Antioquia, Colombia. Then we installed odor devices containing one of the three chemicals on each site and let them there during two weeks. The test was repeated with each of the chemicals in all sites. The number of opossum visits per night was recorded daily using camera-traps with bait and bait+chemical. Results: We found that ammonia and creolin were associated to fewer opossum visits per night. Citronella did not reduce the presence of opossums. In addition, the number of opossums/per night was higher in the urban park compared with the forest reserve. Conclusion: We suggest to further test the repellent effect of ammonia and creolin on real human-opossum conflict scenarios; however, caution is warranted given their irritant, flammable, and corrosive properties.